The versatile interactome of chloroplast ribosomes revealed by affinity purification mass spectrometry - Westrich, Lisa Désirée; Gotsmann, Vincent Leon; Herkt, Claudia; Ries, Fabian; Kazek, Tanja; Trösch, Raphael; Armbruster, Laura; Mühlenbeck, Jens Stephan; Ramundo, Silvia; Nickelsen, Jörg; Finkemeier, Iris; Wirtz, Markus; et al. (Nucleic acids research, 2021)
Abstract. In plant cells, chloroplast gene expression is predominantly controlled through post-transcriptional regulation. Such fine-tuning is vital for precise
Published online 16 December 2020
Gesehen am 01.03.2021